Correspondence: do not overlook parental grief following an infant death in the Neonatal Intensive Care Unit - Hüseyin Çaksen (Journal of Pediatric and Neonatal Individualized Medicine, 2022)
Parents’ bereavement results in high rates of psychological, emotional, physiological, and existential distress after the death of a child during pregnancy, at delivery or in the neonatal period. Parental grief following an infant’s death is usually neglected or overlooked in many Neonatal Intensive Care Units in both developed and developing countries.